Infrastructure Development Planning Based on Local Potential to Increase Farmers Income: (Case Study Porang of Kindang Village, Kindang District, Bulukumba Regency) - Andi Asrul; Basri Bado; Muhammad Syafri; Muhammad Imam Ma'ruf; Diah Retno Dwi Hastuti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to examine the infrastructure planning process based on local conditions and potential, the role of the village government in supporting the development of local porang potential, and the efforts of porang farmers to develop a value chain to increase their income in Kindang Village, Kindang Subdistrict, Bulukumba Regency. This study employs a descriptive qualitative method using a case study approach. Data were collected through interviews, observations, and documentation from 20 informants (village government officials, porang farmers, porang traders, and community leaders), as well as through document analysis of the village medium-term development plan (RPJMDes), the village development work plan (RKPDes), and the village fund budget (DDS). Thematic data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results show that although planning has been carried out in a participatory manner through village meetings, its effectiveness remains limited. The main finding highlights that road quality, especially farm roads, is a key factor in optimizing the value chain and selling price of porang. Limited access increases distribution costs and weakens farmers’ bargaining position, so the economic potential has not been fully utilized. Therefore, strong synergy between participatory planning, strengthening the role of the village government, and infrastructure development oriented toward agricultural production needs is essential to sustainably improve farmers’ income.